EPIDEMIOLOGY OF WRIST PAIN IN AUSTRALIAN GYMNASTS - Beverley Trevithick; Max Stuelcken; Rebecca Mellifont; Mark Sayers (Science of Gymnastics Journal)
Wrist pain in adolescent gymnasts is generally considered a ‘normal’ consequence of the sport. If pain is ignored it may lead to an injury of the distal radial growth plate and subsequent long term wrist dysfunction. There is a lack of epidemiology research on the prevalence of wrist pain in adolescent gymnasts with previous research documenting wrist injuries as part of general injury statistics. We aimed to investigate the life time and point prevalence of wrist pain in Australian gymnasts. A survey was designed to collect data from 10-18 year gymnasts who participated in gymnastics. Data was collected on: (i) historical experience of wrist pain (ii) current wrist pain; (iii) the influence of apparatus on wrist pain; and (iv) treatment modalities utilised. Results found there was a high life time (92.6%) and point prevalence (70.6%) of wrist pain in adolescent gymnasts. When grouped by age there was no significant difference in life time or point prevalence between genders. When grouped by training 1-10 hours per week, females had significantly higher life time prevalence (p = 0.013) than males. When grouped by training 11-25 hours per week males showed a significantly  higher life time prevalence (p = 0.005) and point prevalence (p = 0.004). Wrist braces were reported as the primary method of management for wrist pain. This study promotes research into injury prevention strategies aimed at decreasing the prevalence of wrist pain and the consequence of wrist injury in adolescent gymnasts.